Combination Chemotherapy in Generalized Hodgkin's Disease. Issue 5713 (4th July 1970) - Nicholson, W. M.; Beard, M. E. J.; Crowther, D.; Stansfeld, A. G.; Vartan, C. P.; Malpas, J. S.; Fairley, G. Hamilton; Scott, Ronald Bodley
Abstract : Fifty-two patients with generalized Hodgkin's disease were treated with a combination of mustine hydrochloride, vinblastine, procarbazine, and prednisolone. Complete remissions were obtained initially in six out of seven patients (86%) who had previously received no treatment, in 15 out of 19 (79%) who had had only radiotherapy in the past, and in 9 out of 26 (35%) who had previously been given chemotherapy with or without radiotherapy. Of these 30 patients in whom a complete remission was obtained 22 have been free of any symptoms or signs of disease for periods ranging from 4 to 22 months. The response to treatment was rapid, and toxicity was not a major problem, except in those who had previously been treated with cytotoxic drugs used continuously and not in courses. A comparative trial of radiotherapy and combination therapy in the treatment of Stage III Hodgkin's disease is strongly recommended.